2021
DOI: 10.1145/3479574
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Authenticity on TikTok: Social Norms and Social Support on the "Fun" Platform

Abstract: Authenticity, generally regarded as coherence between one's inner self and outward behavior, is associated with myriad social values (e.g., integrity) and beneficial outcomes, such as psychological well-being. Scholarship suggests, however, that behaving authentically online is complicated by self-presentation norms that make it difficult to present a complex self as well as encourage sharing positive emotions and facets of self and discourage sharing difficult emotions. In this paper, we position authenticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 79 publications
1
31
0
3
Order By: Relevance
“…As this research is focusing on exploring the students behavior in using TikTok, the data of the research is described on the following table; The result from the question no 1 shows that the students are giving positive response for the TikTok on their daily life. This finding is similar with the research by Barta and Andalibi (2021) on their research entitled Constructing Authenticity on TikTik: Social Norms and Social Support on the "Fun" Platform. The research found that the TikTok can be fun for its user due to the presenting the online space for support of the society as well as the connection with other people, it is also including sharing the positive emotion among people on this platform.…”
Section: Resultssupporting
confidence: 90%
“…As this research is focusing on exploring the students behavior in using TikTok, the data of the research is described on the following table; The result from the question no 1 shows that the students are giving positive response for the TikTok on their daily life. This finding is similar with the research by Barta and Andalibi (2021) on their research entitled Constructing Authenticity on TikTik: Social Norms and Social Support on the "Fun" Platform. The research found that the TikTok can be fun for its user due to the presenting the online space for support of the society as well as the connection with other people, it is also including sharing the positive emotion among people on this platform.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, users may adjust the content of their posts based on whether their content was anonymous or not. Perceived anonymity on TikTok may be linked to users' perceptions of the platform as a space to share authentic everyday interactions (Barta and Andalibi, 2021).…”
Section: Meaning Making and Relatednessmentioning
confidence: 99%
“…The public presentation of Singh as an “authentic politician” (Enli, 2015, p. 110) and his playful use of TikTok is situated within larger discussions of authenticity, celebrity, and influencers in political communication on social media (Barta & Andalibi, 2021; Luebke, 2021; Luebke & Engelmann, 2022). Authenticity is a challenging notion to define, and scholarship pertaining to political communication has approached the concept as an imaginary ideal mediating a politician’s “real” or “true” personality for strategic gain in electoral campaigns (Dumitrica, 2014; Gaden & Dumitrica, 2015).…”
Section: Overview Of Literaturementioning
confidence: 99%